Metasubject approach to teaching geography on the example of studying the life of the Eskimos - Galina S. Samigullina (Publishing house "Sreda", 2023)
The purpose of the work is to substantiate the meta-subject approach to teaching geography on the example of studying the life of ethnic groups. Based on the methods of analysis of psychological and pedagogical literature and technological maps of lessons taken from teachers' websites; designing the meta-subject content of educational tasks in the course of school geography, the need to use the subject and meta-subject approach in their totality was identified and justified. The author's assignments for the development of basic logical actions among students and the formation of interdisciplinary concepts were developed with the involvement of knowledge, methods of activity and concepts of related disciplines on the example of studying the life and life of the Eskimos in the subarctic tundra. The meta-subject approach made it possible to realize the pedagogical potential of geography in the educational process using the knowledge of history, biology, physics, and chemistry. Interdisciplinary concepts were revealed in the study of the dwellings of the Eskimos. The results of the study were tested in the system of advanced training for teachers of geography, biology, chemistry, physics; in the system of training future teachers of geography and ecology. The developed complex integrated tasks, in which universal learning activities require a logical continuation using interdisciplinary concepts, can be used in the study of disciplines at the bachelor's-lauric level "Project activity in education", the master's program "Formation of meta-subject learning outcomes in geography".